2002
DOI: 10.1021/bi011781z
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Dynamics of the JE-2147−HIV Protease Complex:  Drug Resistance and Thermodynamic Binding Mode Examined in a 1.09 Å Structure,

Abstract: The structure of HIV protease (HIV Pr) bound to JE-2147 (also named AG1776 or is determined here to 1.09 Å resolution. This highest-resolution structure for HIV Pr allows refinement of anisotropic displacement parameters (ADPs) for all atoms. Clustering based on the directional information in ADPs defines two sets of subdomains such that within each set, subdomains undergo similar anisotropic motion. These sets are (a) the core of monomer A grouped with both substrate-binding flaps and (b) the core of monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 40 publications
4
63
1
Order By: Relevance
“…Inhibitor 1 was bound in two conformations in all structures in the space group P2 1 2 1 2 with relative occupancy of 0.6/0.4, although it had a single conformation in the PR V82A complex in space group P2 1 2 1 2 1 ( Figure 2). Alternate conformations were observed for the main chain atoms of residues 3-5 in PR V82A , as noted previously in complexes PR V82A /darunavir [PDB code 2IDW] 11 and PR/JE-2147 [PDB code 1KZK] 19 . There were 23 residues with two alternate conformations modeled for the side chains in PR, 23 for mutant PR D30N , 29 for PR I50V , 22 for PR V82A and 25 for PR I84V .…”
Section: Residues With Alternate Conformationssupporting
confidence: 80%
“…Inhibitor 1 was bound in two conformations in all structures in the space group P2 1 2 1 2 with relative occupancy of 0.6/0.4, although it had a single conformation in the PR V82A complex in space group P2 1 2 1 2 1 ( Figure 2). Alternate conformations were observed for the main chain atoms of residues 3-5 in PR V82A , as noted previously in complexes PR V82A /darunavir [PDB code 2IDW] 11 and PR/JE-2147 [PDB code 1KZK] 19 . There were 23 residues with two alternate conformations modeled for the side chains in PR, 23 for mutant PR D30N , 29 for PR I50V , 22 for PR V82A and 25 for PR I84V .…”
Section: Residues With Alternate Conformationssupporting
confidence: 80%
“…From the results of 22 nanosecond-long, conventional, all-atom, explicitly solvated molecular dynamics simulations of a wild type (1KZK.pdb) 2 and of the V82F/I84V drug-resistant mutant of HIV-1 protease, valine 82 mutated to phenylalanine and isoleucine 84 mutated to valine (1D4S.pdb), 3 a plausible reason to explain the drug-resistant properties of that double mutant was discovered. 4 Those molecular dynamics (MD) experiments indicated that the mechanism of drug resistance for that double mutant potentially involves a shift in its ensemble of conformations such that the mutant favors the semiopen structures more than the wild-type protease prefers them.…”
Section: Introductionmentioning
confidence: 99%
“…Because the restraints utilized to generate the data shown by the blue histogram were chosen to mimic the effects of an allosteric flap opener, the symbol AFO is included for that line of the figure legend. For comparison, distance L had a value of 15.0 Å in the closed crystal structure of the complex of HIV-1 protease with an active-site inhibitor (1KZK.pdb) 2 , and it had a value of 19.7 Å in the semiopen crystal structure of the apo HIV-1 protease (1HHP.pdb). 14 respectively (both are inhibitor-bound, closed complexes).…”
Section: Introductionmentioning
confidence: 99%
“…The data given in Tables 1 and 2, in which the solventaccessible surface area (SASA) was calculated for the 39 available ensemble members in the structure of a transcriptional antiterminator (PDB entry 3gwh; Rodríguez et al, 2009) and for the first 50 ensemble members, out of a total of 600, in the structure of HIV hydrolase (PDB entry 1kzk; Reiling et al, 2002), show a random distribution of a variable that quantitatively represents the shape of the proteins. Differences in the SASA in the crystal contacts of the selection of ensemble members studied for 3gwh reached 11%, whereas the changes in the total SASA were 13%.…”
Section: Resultsmentioning
confidence: 99%